Fortified settlements and the settlement system in the Northern Zone of the Han Empire. (March 2014) - Bo, Chen; Shelach, Gideon
Abstract : How far are settlement patterns affected by imperial systems of administration and control? The prototype city state consisted perhaps only of the population centre and its surrounding hinterland, but large territorial states, and still more empires, required complex systems of government and defence. Historical sources tell of the Chinese imperial system of 'commanderies' or provinces, and 'county seats' or subordinate centres, but this may conceal a range of local variations and development histories that only detailed archaeological survey can reveal. In this study, devoted to the Northern Zone of the Han Empire close to its border with the troublesome Xiongnu, a four-fold hierarchy of walled settlements is presented which varies in its character, origins and development even within this single zone. Many of its special features can be attributed to the pressures and insecurities of the border setting, and are the direct result of Han imperial planning.